TIPOLOGI SINTAKSIS DALAM BAHASA BATAK MANDAILING - Evi Marlina Harahap (Jurnal Hata Poda, 2022)
This study discusses the word order of the Mandailing language in a syntactic typology review. In collecting data, the method of listening and literature review was used. In reviewing the data needed in this paper, the agih method is used. The results of data analysis in this paper are presented with informal methods and formal methods. In the Mandailing Batak language, there are two types of word order. Verbal word order and nominal word order. The dominant order pattern is found in sentences that begin with a verb and are followed by a noun that functions as a subject. While the alternative order pattern is found in the nouns that fill the function of the subject and object which are put forward. The word order in the Mandailing Batak language has a V-S-O dominant pattern, and the alternative sequence pattern is S-V-O, OVS, V-O-S. In the SVO sequence in the Mandailing language, the elements that fill the S function can be filled by three categories, namely nouns, personal pronouns, and demonstrative pronouns. The word order of type VOS is a variant of the word order of type SVO. This word order has two kinds of models. The first model is an element of the subject function filler category consisting of definite nouns, the second model is an element of the subject function filler category consisting of non-definite nouns. Keyywords: linguistic, typology, syntax, Mandailing’s language.